A new educational program in heart failure drug development: the Brescia international master program. Issue 8 (August 2018) - Dungen, Hans-Dirk; Petroni, Renata; Correale, Michele; Coiro, Stefano; Monitillo, Francesco; Triggiani, Marco; Leone, Marta; Antohi, Elena-Laura; Ishihara, Shiro; Sarwar, Chaudhry M.S.; Sabbah, Hani N.; Memo, Maurizio; et al.
Abstract : N/A: Despite recent advances in chronic heart failure treatment, prognosis of acute heart failure patients remains poor with a heart failure rehospitalization rate or death reaching approximately 25% during the first 6 months after discharge. In addition, about half of these patients have preserved ejection fraction for which there are no evidence-based therapies. Disappointing results from heart failure clinical trials over the past 20 years emphasize the need for developing novel approaches and pathways for testing new heart failure drugs and devices. Indeed, many trials are being conducted without matching the mechanism and action of the drug with the clinical event. The implementation of these novel approaches should be coupled with the training of a new generation of heart failure physicians and scientists in the art and science of clinical trials. Currently, drug development is led by opinion leaders and experts who, despite their huge personal experience, were never trained systematically on drug development. The aim of this article is to propose a training program of 'drug development in Heart Failure'. A physician attending this course would have to be trained with a major emphasis on heart failure pathophysiology to better match mechanisms of death and rehospitalization with mechanism of action of the drug. Applicants will have to prove their qualifications and special interest in heart failure drug development before enrollment. This article should serve as a roadmap on how to apply emerging general principles in an innovative drug-development-in-heart-failure-process as well as the introduction of a new educational and mentorship program focusing on younger generations of researchers.